Psychoeducation through Storytelling, Movement, and Song to Enhance Learning Concentration in TPA Children, Pakis, Magelang - Dhyatmika, Mahatma Acintya; Hermahayu, Hermahayu; Zahra, Aning Az (Universitas Negeri Surabaya, 2024)
Background: Children may face a difficulty in maintaining concentration during learning sessions, a factor that varies among individuals. At TPA (Quranic Education Center) Uswatun Khasanah Banyusidi, Pakis, Magelang, students also encounter issues with concentration and focus in their studies. Objective: This study aims to achieve several objectives: (1) assess the level of a child's learning concentration, (2) explore how psychoeducation, using storytelling, movement games, and songs, can improve a child’s concentration, and and (3) evaluate the effectiveness of psychoeducation in enhancing a child’s learning concentration. Method: The research adopts a classroom action research design, comprising two cycles. The process involves planning, implementing interventions, observing outcomes, and reflecting on results. Results: After Cycle 1, 41.02% of children met the expected development criteria, increasing to 79.48% in Cycle 2, with 53.84% meeting expected development and 25.64% demonstrating excellent progress. Conclusion: The use of psychoeducation through storytelling, movement, and songs at TPA (Quranic Education Center) Uswatun Khasanah Dayugo has successfully improved children’s learning concentration in each session.Abstrak Latar Belakang: Anak mungkin mengalami kesulitan dalam menjaga konsentrasi saat pembelajaran, faktor yang berbeda-beda pada setiap individu. Di TPA (Pusat Pendidikan Al-Quran) Uswatun Khasanah Banyusidi, Pakis, Magelang, siswa juga mengalami kendala konsentrasi dan fokus dalam belajar. Tujuan: Penelitian ini bertujuan untuk mencapai beberapa tujuan: (1) menilai tingkat konsentrasi belajar anak, (2) mengeksplorasi bagaimana psikoedukasi, dengan menggunakan bercerita, permainan gerak, dan lagu, dapat meningkatkan konsentrasi anak, dan (3) mengevaluasi efektivitas psikoedukasi dalam meningkatkan konsentrasi belajar anak. Metode: Penelitian ini menggunakan desain penelitian tindakan kelas, yang terdiri dari dua siklus. Prosesnya meliputi perencanaan, pelaksanaan intervensi, pengamatan hasil, dan refleksi hasil. Hasil: Setelah Siklus 1, 41,02% anak memenuhi kriteria perkembangan yang diharapkan, meningkat menjadi 79,48% pada Siklus 2, dengan 53,84% memenuhi perkembangan yang diharapkan dan 25,64% menunjukkan kemajuan sangat baik. Kesimpulan: Penggunaan psikoedukasi melalui bercerita, gerak, dan lagu di TPA (Pusat Pendidikan Quran) Uswatun Khasanah Dayugo berhasil meningkatkan konsentrasi belajar anak pada setiap sesinya.